Comparative study on effect of different embryo culture media on in vitro blastocyst production in goats - GOEL, PUJA; GOEL, A K; BHATIA, A K; KHARCHE, S D (The Indian Journal of Animal Sciences, 2016)
The present study was aimed to assess the efficacy of different culture media for blastocyst development. Oocytes (2,539) from 1,059 ovaries recovered by follicle puncture technique were utilized for present investigation. In experiment 1, effect of different embryo culture media (Gr. 1; mKSOMaa; Gr. 2; TCM-199+OEC; Gr. 3; mSOFaa and Gr. 4; mCR2aa) and in experiment 2, effect of sequential embryo culture medium, Gr. 1: mKSOMaa containing 5% FBS (1–3 days) and 10% FBS (4–10 days); Gr. 2: 0.8% BSA (1–3 days) and continuous embryo culture medium, 10% FBS (4–10 days); Gr. 3: 0.8% BSA (1–10 days) and Gr. 4: 10% FBS (1–10 days) on in vitro blastocyst development potential was evaluated. Significant higher (P